(untitled) (Impact: Journal of Transformation, 2022)
This study analyzed factors affecting youth employment in Ngong and Ongata Rongai wards in Kajiado North Constituency, Kenya. The study was guided by four specific objectives: to find out national and county government initiatives’ effect on youth employment; establish whether life-skills training affects youth employment; examine whether cultural dynamics affects youth employment; and find out whether mentorship training affected youth employment. The study applied the descriptive research design targeting a population of 33,326 respondents consisting of the two youth officers in Kajiado North Sub-County and youth from the 2 wards in which 395 participants were selected using stratified simple random sampling. The data was collected using primary and secondary sources, where a questionnaire was used to gather data. The results showed that a majority of the youths were not employed. The correlation results indicated that there was a positive and statistically significant association between government interventions, life skills, cultural dynamics, mentorship training, and youth employment implying that these variables moved in the same direction. The linear regression analysis revealed that the model was statistically significant as shown by p=0.000. The report for regression results showed a significance level of less than 0.05. An increase in government interventions and mentorship training resulted in an increase in youth employment and this was statistically significant (P=0.000) An increase in life skills resulted in an increase in youth employment (P=0.149). An increase in cultural dynamics resulted in a reduction in youth employment but this was not significant with the value of (P=0.959). The study recommends that monitoring and evaluation of county and national government interventions be carried out, enforcement of mentorship programs through regulatory framework and provision of more information on how to implement and measure a mentorship program.